2023
DOI: 10.3389/fimmu.2023.1171671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of PD-1 inhibitors in specific subgroups of patients with advanced esophageal squamous cell carcinoma: a systematic review and meta-analysis of phase 3 randomized clinical trials

Abstract: PurposeIn recent years, a number of clinical trials have shown that programmed death 1 (PD-1) inhibitors offer significant survival benefits in patients with esophageal squamous cell carcinoma (ESCC). We conducted a meta-analysis to explore the antitumour efficacy of PD-1 inhibitor-based therapy in specific subgroups of patient with advanced ESCC.MethodsWe searched for eligible studies from the PubMed, Embase, Web of Science, Cochrane Library databases and conference abstracts. The indicators related to surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…This hypothesis was primarily supported by the growing evidence of the favorable outcomes observed in patients with elevated expression levels of immune checkpoint molecules following ICI therapy. 37 , 38 Furthermore, our analysis of reference immune cell datasets, specifically PBMC-R and PBMC-NR, indeed displayed higher expression of exhausted T cell markers.…”
Section: Discussionmentioning
confidence: 70%
“…This hypothesis was primarily supported by the growing evidence of the favorable outcomes observed in patients with elevated expression levels of immune checkpoint molecules following ICI therapy. 37 , 38 Furthermore, our analysis of reference immune cell datasets, specifically PBMC-R and PBMC-NR, indeed displayed higher expression of exhausted T cell markers.…”
Section: Discussionmentioning
confidence: 70%
“…Another milestone multi-omics study subtyping lung SCC identified a "classical" subtype featuring amplification and expression of TP63/ΔNp63 along with downregulation of immune signaling (59). Immunotherapy has been increasingly explored and utilized in ESCC and lung SCC management (68,69). Identifying patients responsive to immunotherapy is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The disease burden of oesophageal cancer is particularly significant in China [1,4], the disability-adjusted life years (DALYs) caused by oesophageal cancer ranks fourth among all cancers [5]. Advanced OSCC has a poor prognosis, with a 5-year survival rate of approximately 15-25% [6]. The efficacy of conventional chemotherapy regimens for advanced OSCC is limited, with less than one year of overall survival for patients treated with first-line cisplatin in combination with paclitaxel or fluorouracil regimens [6][7][8].…”
Section: Introductionmentioning
confidence: 99%